PENGARUH PENGGUNAAN MEDIA E-FLASHCARD TERHADAP PENGETAHUAN SISWA MENGENAI PENCEGAHAN COVID-19 TAHUN 2021 (Jurnal Kesehatan Siliwangi, 2021)
Corona Virus Disease 2019 (COVID-19) is a disease caused by a new type of corona virus named SARS-CoV-2. People who have a high vulnerability to COVID-19, one of which is the Indonesian Pediatrician Association (IDAI) stated that the child mortality rate due to COVID-19 in Indonesia is the highest in ASEAN. One of the efforts to prevent COVID-19 is to wash hands with soap and use masks properly and correctly. This study aims to determine the effect of using e-flashcard media on students' knowledge of COVID-19 prevention at SDN Lagadar 05 Margaasih District, Bandung Regency 2021. This research was conducted using a pre-experimental method with a one group pre test post test design. The population of this study were all students at SDN Lagadar 05 as many as 168 students. A sample of 69 students was determined by using stratified sampling technique. The data collection method used the observation, questionnaire, and documentation methods. The instrument was tested for validity and tested for reliability. The results showed that: 1) This study produced a product in the form of an e-flashcard media about COVID-19 prevention, with the results of the media and material validity test being 100% 2) Students' knowledge of COVID-19 prevention efforts before 50.43 and after 76.23 given e-flashcard media. 3) There is an effect of using e-flashcard media on students' knowledge about preventing COVID-19 with the Wilcoxon test result that is 0.000 < 0.005. Therefore, it can be concluded that e-flashcard media is very feasible as a health promotion media and e-flashcard media has an impact on students' knowledge about COVID-19 prevention at SDN Lagadar 05 Margaasih District, Bandung Regency 2021.